STRUCTURE OF INTELLECTUAL TREND IN RECENT RESEARCHES ON ‘ISLAM’: AN APPROACH TO CONSOLIDATE THE EMPIRICAL STUDIES - Masoom, Muhammad Rehan (Journal of Al-Tamaddun, 2012)
No other religion has become such a big controversial issue as Islam does. Islam has become a buzzword in the modern world, especially after 9/11. It is no more mere a religion; it has integrated a lot more political and social facets into it. Hundreds of intellectuals of different corners of the world have made themselves engaged in developing perspectives to explain political forms in Islamic world, Islamism, Islamic State, Jihad, Martyrdom or Shahadah and so forth. Though it may seem the researchers are involved in analyzing different aspects of Islam, integration is possible to understand it in a more comprehensive manner. This paper would provide a straightforward guideline to grasp most of the pertinent aspects related to the intellectual trends of the researchers on Islam in the last few decades.